Determination of bow sight settings using arrow ballistics, initial measurements of bow and arrow geometry and initial arrow velocity - Kouba, James Jr (My University, 2000)
Historically, problems in archery have been solved primarily by the trial and error method. Of these problems, one deals with the increasing popular use of the bow sight as a sighting aid. The problem arises in setting the sight for various distances so that the desired amount of accuracy is achieved. This leads to three areas of difficulty. First, how does the novice archer set the sight setting when their ability does not allow for small enough arrow groups to determine group center. Second, as the shooting distance becomes longer, generally the arrow grouping grows in size thus expanding the group to a size too large in order to determine group center. Third, the archer does not have access to a shooting area of adequate dimensions or does not possess the time required to effectively use the trial and error method. The intent of this paper is two fold. First, to use aerodynamics and arrow ballistics with elementary bow and arrow geometry to determine these sight settings; theoretically, thereby eliminating the need for trial and error. This method should only need a minor adjustment at the desired distances to be effective. Second, to learn the Mathcad computer program.
Plan B Paper. 2000. Master of Science in Education-Physics--University of Wisconsin-River Falls. Physics Department. 18 leaves. Includes bibliographical references (leaf 18).
Keywords: Bow sight settings; Bow and arrow geometry; Arrow velocity; Archery; Physics--Experiments; Bow and arrow; Physics; Bow and arrow--Experiments